2017
DOI: 10.3349/ymj.2017.58.3.527
|View full text |Cite
|
Sign up to set email alerts
|

Rare Frequency of Mutations in Pituitary Transcription Factor Genes in Combined Pituitary Hormone or Isolated Growth Hormone Deficiencies in Korea

Abstract: PurposeCongenital hypopituitarism is caused by mutations in pituitary transcription factors involved in the development of the hypothalamic-pituitary axis. Mutation frequencies of genes involved in congenital hypopituitarism are extremely low and vary substantially between ethnicities. This study was undertaken to compare the clinical, endocrinological, and radiological features of patients with an isolated growth hormone deficiency (IGHD) or combined pituitary hormone deficiency (CPHD).Materials and MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Poorly developed sella turcica is associated with LHX4 mutations ( 9 ). Additionally, LHX3 and LHX4 mutations are associated with Chiari I malformation, corpus callosum agenesis or hypoplasia and skeletal abnormalities ( 10 ). Specific genetic mutations in CPHD patients are not frequently identified.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly developed sella turcica is associated with LHX4 mutations ( 9 ). Additionally, LHX3 and LHX4 mutations are associated with Chiari I malformation, corpus callosum agenesis or hypoplasia and skeletal abnormalities ( 10 ). Specific genetic mutations in CPHD patients are not frequently identified.…”
Section: Discussionmentioning
confidence: 99%
“…Lithuania for PROP1 gene) or in cases with a specific hormonal, neuroradiological or extra-pituitary phenotype. By contrast, the genetic screening of pituitary transcription factors should not be part of routine work-up for Western-European sporadic patients with MPHD, as also suggested by other authors [ 15 17 ].…”
Section: Introductionmentioning
confidence: 93%
“…However, the endocrine phenotypes of all these mutations may be characterized by variable degrees of anterior pituitary hormone deficiency, ranging from isolated GHD to the complete failure of all anterior pituitary cell lineages and this complex hormonal picture may be furtherly complicated by a possible evolution of the endocrinological status over the life-span of the same patient [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of GHD include pituitary dysplasia and pathogenic mutations in GH-insulin like growth factor 1 (IGF1) axis-related genes, such as GH1 , GHRHR ( 3 , 4 ). However, recent cohort studies of the genetic causes of GHD patients in South and East Asian populations reported that the proportion of patients with molecular diagnosis ranges from 4% to 43% ( 5 , 6 ). The undiagnosed rate indicates that there are still a lot of unknowns about the genetic predispositions of GHD.…”
Section: Introductionmentioning
confidence: 99%